Investigation of effects of neurotrophic factors on painful diabetic neuropathy: an experimental study - Kilinc, Faruk; Colak, Ramis; Ozcan, Mete; Ayar, Ahmet (My University, 2019)
Objective: We have studied the effects of neurotrophin-4 (NT-4) different doses on the pain levels ofstreptozocin-induced diabetic rats.Methods: Thirty-five 3-week-old male rats were used. After induction of diabetes in rats with streptozocin(nearly 4 weeks); diabetic animals were divided into 4 groups. The first group; healthy control group (n = 15),the second group; diabetic control group (n = 10 ), the third group; low dose (0.3 mg/ kg ) recombinant humanNT-4 was applied (n = 4 ) and the fourth group; high dose recombinant human NT-4 was applied (n = 6).Results: In the low-dose NT-4 group, the pain threshold values did not differ from the diabetic control andhealthy control groups. In the high dose NT-4 group, a rise was observed in the pain threshold values of hotplate in comparison with the healthy control group, diabetic control group and low dose applied group and thisrise reached at the level of statistical significance (p < 0.05).Conclusion: Neurotrophic factors (neurotrophin-4) have been shown to be effective on painful diabeticneuropathy in streptozocin-induced diabetic rats. However, there is a need for larger-scale and longer-termstudies for clinical use.
Keywords: Periferik Damar Hastalıkları; Genel ve Dahili Tıp